Modeling regional supply responses using farm-level economic data and a biophysical model: A case study on Brazilian land-use change - Samuel Balieiro (Johann Heinrich von Thünen-Institut, 2023)
Estimating farmers' supply responses to changes in framework conditions is important to in-form decision-makers on the expected impacts on production volume as well as the resulting land-use shifts. Existing agricultural supply response models generally require either larger databases with farm-level data for microregional analysis or are implemented with a coarse resolution (e.g., country level) due to the lack of data. While such approaches are suitable for regions with abundancy of data or for global-scale analysis, there is a need for an alternative for micro-level analysis in countries with low data availability. In addition, it is important to include the spatial component in the regional supply response analysis, allowing not only the quantification of the overall change in output but also the likely spatial land-use change. Against this background, this dissertation aims to answer the research question whether a combination of a biophysical model with farm-level economic data can be used to estimate farm-level profitability of individual crops and respective cropping systems and thereby simulate farmers' supply responses in countries with limited data availability. To answer this ques-tion, a new modeling approach called Profitability Assessment Model (PAM) is developed, tested and validated. This new modeling approach follows the principles of minimum data, focusing on delivering timely and quantitative analyses with satisfactory accuracy to inform decision-makers. That is an important feature since the overall goal of the concept is to limit the data required by the model to a minimum, allowing quick implementation while accepting moderate accuracy. [...] – – Die Schätzung der Angebotsreaktionen von Landwirten auf veränderte Rahmenbedingungen ist wichtig, um Entscheidungsträger über die erwarteten Auswirkungen einer Maßnahme auf das Produktionsvolumen und die daraus resultierenden Landnutzungsänderungen zu informieren. Bestehende Modelle für landwirtschaftliche Angebotsreaktionen erfordern in der Regel entweder größere Datenbanken für mikroregionale Analysen auf Betriebsebene oder werden aufgrund fehlender Daten mit einer groben Auflösung (z. B. auf Länderebene) implementiert. Solche Ansätze eigenen sich für Regionen mit einer hohen Datenverfügbarkeit oder für Analysen auf globaler Ebene. Für die Analyse auf Mikroebene, in Ländern mit geringer Datenverfügbarkeit, bedarf es jedoch eines alternativen Ansatzes. Darüber hinaus ist es wichtig, die räumliche Komponente in die Analyse der regionalen Angebotsreaktion einzubeziehen, um nicht nur die Gesamtveränderung der Produktion sondern auch die anzunehmende räumliche Landnutzungsänderung quantifiziert zu können. Vor diesem Hintergrund soll in dieser Dissertation die Forschungsfrage beantwortet werden, ob die Kombination eines biophysikalischen Modells mit ökonomischen Daten auf einzelbetrieblicher Ebene dazu verwendet werden kann, um die Rentabilität einzelner Kulturen und entsprechender Anbausysteme auf Betriebsebene zu schätzen. Insbesondere sollen mit diesem Ansatz die Angebotsreaktionen von Landwirten in Ländern mit begrenzter Datenverfügbarkeit simuliert werden. Zur Beantwortung dieser Frage wird ein neuer Modellierungsansatz, das Profitability Assessment Model (PAM), entwickelt, getestet und validiert. Dieser neue Modellierungsansatz folgt dem Prinzip des Mindestdatensatzes und konzentriert sich darauf zeitnahe und quantitative Analysen mit zufriedenstellender Genauigkeit zu liefern, um eine gesonderte Informationsbasis für Entscheidungsträger zu schaffen. Dies ist ein wichtiges Merkmal, da das Gesamtziel des Konzepts darin besteht, die für das Modell erforderlichen Daten auf ein Minimum zu beschränken, sodass eine schnelle Umsetzung bei zufriedenstellender Genauigkeit möglich ist. [...]
urn:nbn:de:gbv:253-202304-dn066229-6
Keywords: 630; Brazil; Land-use change; Biophysical model; Production costs; Supply analysis; Soybeans; Maize; Sugarcane; Climate change; Profitability; Brasilien; Landnutzungsänderung; Biophysikalisches Modell; Produktionskosten; Angebotsanalyse; Sojabohnen; Mais; Zuckerrohr; Klimawandel; Wirtschaftlichkeit